(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses not only studies of the chemical composition of the plant Urtica dioica, but also its medicinal properties. The amount of macronutrients, trace elements and heavy metals in the Urtica dioica leaf (six yellow areas), Bundy and flower was studied, as well as their distribution by region with an explanation of the reasons.